Effects of supporting facilities on memory loss among older people with dementia in care and attention homes. Issue 3 (March 2020) - Leung, Mei-yung; Wang, Chendi; Kwok, Timothy CY
Supporting facilities (SF) including handrails, signage, finishes, furniture and recreational facilities facilitate the daily life of older persons. Memory loss is one of the most common signs of dementia affecting the daily life of older persons. Therefore, they may need special SF in residential homes. In order to improve the quality of daily life of older people with dementia, this study aims to investigate the effects of SF on the memory loss of those living in care and attention (C&A) homes. A questionnaire survey was conducted among elderly C&A home residents aged 65 and above in Hong Kong. A Supporting Facilities-Memory Loss model was established based on correlation and regression analyses. The model confirmed the following: (1) none of the SF items affects long-term memory loss; (2) satisfaction with signage, finishes and furniture leads to a reduction of short-term memory loss; (3) satisfaction with handrails, signage and finishes enhances spatial memory and (4) satisfaction with the location of signage reduces time confusion. Practical recommendations are proposed, including using large and well-placed signage with pictograms and icons, avoiding the removal and modification of furniture, enhancing colour contrasts between different functional rooms, installing handrails with a consideration for orientation strategies, and so on.